Non-ionic resins and mixtures of non-ionic resins and cationic additives for antifouling building compositions

By combining cationic additives with nonionic resins, the water sensitivity problem of existing water-based building compositions when preventing stain migration is solved, achieving better stain resistance and paint film performance.

CN119546708APending Publication Date: 2025-02-28BENJAMIN MOORE & CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052489.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing water-based building compositions have water sensitivity problems in preventing stain migration, resulting in reduced wet adhesion, scrubbing resistance and foaming resistance.

Method used

Using a novel aqueous building composition, a composition with improved stain resistance and reduced water sensitivity is formed by combining cationic additives with nonionic resins, using the tannin locking function of the cationic additives, combined with the stability and compatibility of the nonionic resin.

Benefits of technology

It realizes that the stains are effectively prevented from moving from the substrate to the topcoat without increasing water sensitivity, while improving the foam resistance and durability of the paint film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231983740000082
    Figure BDA0005231983740000082
  • Figure BDA0005231983740000091
    Figure BDA0005231983740000091
  • Figure BDA0005231983740000103
    Figure BDA0005231983740000103
Patent Text Reader

Abstract

Disclosed herein are nonionic resin compositions that polymerize without or substantially without acid monomers. The nonionic resin composition is compatible with a cationic additive to lock stains. Primer and topcoat compositions containing such compositions are capable of preventing migration of stains to the top of the paint film.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to low VOC, waterborne, antifouling building compositions, including but not limited to primer or topcoat compositions comprising a cationic additive mixed with a nonionic latex resin.

[0002] The present invention also relates to nonionic resins. Background of the Invention

[0004] Certain substrates to be painted, such as wood, contain tannins, which are astringent polyphenolic biomolecules that can penetrate paint films (including primer layers) and stain topcoat layers, becoming undesirable visible stains on the painted substrate. Other stains include crayons, lipstick, markers, coffee, wine, etc. and other stains on walls, and water stains on ceilings, which can penetrate paint films.

[0005] Conventional solvent-based alkyd coatings block stains but have odor and high volatile organic component (VOC) emissions. Hydrophobic waterborne acrylic resins have been used to block stains by forming a hydrophobic paint film layer. In these hydrophobic waterborne systems, stains still penetrate into the primer layer and eventually the topcoat.

[0006] Most stains are anionic in nature and can be prevented from migrating by cationic resins in waterborne building compositions. Cationic resins restrict the migration of water-soluble stains in waterborne coating applications. Cationic resins form complexes with anionic stains in an ion exchange setting, rendering the stains insoluble and trapped or locked in the primer film as it dries. However, cationic resins are generally highly hydrophilic and can increase the water sensitivity of building compositions and paint films. Increased water sensitivity in cationic coatings can result in loss of wet adhesion, scrub resistance, and blister resistance.

[0007] As discussed in U.S. Pat. No. 5,312,863, conventional water-based latex coatings are typically anionic. Anionic latex polymer binders are typically prepared by aqueous emulsion polymerization techniques using nonionic and / or anionic surfactants. These anionic latex polymer binders are blended with opacifying pigments, extender pigments, and dispersed with anionic pigment dispersants to form water-based latex coatings or paints. The anionic binders typically contain anionic functional groups such as sulfate and carboxylate groups. Functionalization of these anionic latex polymers with amines, acetoacetates, or amides (such as ethylene urea derivatives) can improve wet adhesion to substrates. The '863 patent and the references cited therein are incorporated by reference in their entirety.

[0008] However, heretofore, cationic resins have not been blended or mixed with anionic resins to alleviate the water sensitivity problems associated with cationic resins. Blending or mixing cationic resins with anionic resins tends to result in coarse particle formation or gelation and generally results in a loss of performance and physical properties.

[0009] Therefore, there remains a need for waterborne formulations that have improved stain resistance and that can prevent the migration of stains from the substrate to the topcoat while minimizing the water sensitivity of the paint film.

[0010] More specifically, there remains a need for nonionic resins that can be mixed with cationic additives or other additives that can inhibit the migration of stains from the substrate into the topcoat.

[0011] There remains a need for improved nonionic resins. Summary of the invention

[0012] Thus, the present invention relates to novel waterborne building compositions that combine cationic additives with novel waterborne compositions that can lock in stains. Preferably, the novel waterborne compositions include a nonionic waterborne resin composition as a carrier for the cationic additive or other tannin reactive compounds. The nonionic resin composition of the present invention is stable and compatible with the cationic additive.

[0013] In order to avoid water sensitivity issues associated with cationic resins when used in paints, preferably in embodiments of the present invention, cationic additives are preferably used instead of cationic resins to provide tannin locking functionality. Preferably, the cationic additives are mixed with the nonionic resins of the present invention.

[0014] The present invention also relates to the inventive nonionic resin. Preferably, the inventive nonionic resin is compatible with the cationic additive or the tannin-reactive compound.

[0015] Advantageously, as disclosed in parent U.S. Provisional Patent Application Serial No. 63 / 388,080 filed on July 11, 2022, the nonionic resins of the present invention are also compatible with cationic resins so that blending the two resins does not form coarse particles or gels.

[0016] Preferably, the nonionic resin of the present invention contains no or substantially no acid monomers, such as monomers with carboxylic acids, and contains no or substantially no monomers with anionic groups, such as monomers with phosphates, sulfonates, and other anionically charged monomers. As used herein, substantially free of monomers (e.g., acid monomers and anionically charged monomers) refers to a low level of less than 0.25 wt%, preferably less than 0.125 wt%, more preferably less than 0.1 wt% of the total monomer content. More preferably, the nonionic resin of the present invention contains no acid monomers, i.e., substantially no acid monomers or other monomers with anionic groups.

[0017] Without being bound by any particular theory, the inventors of the present invention have found that when a polymerizable nonionic hydrophilic component (such as a polymerizable polyethylene glycol monomer or a polymerizable polypropylene glycol monomer) is copolymerized with a film-forming monomer and a nonionic surfactant to form micelles, polymerization (preferably emulsion polymerization) can be carried out in the absence of an acid monomer. In one embodiment, the only surfactant used to form micelles and latex particles is a nonionic surfactant.

[0018] The nonionic surfactant is preferably present in less than about 5 wt%, preferably about 1 wt% to about 4 wt%, preferably about 1.5 wt% to about 3.5 wt%. Alternatively, the nonionic surfactant is present in about 1 wt% to about 4.5 wt%, preferably about 1.25 wt% to about 4.25 wt%, and preferably about 1.5 wt% to about 3.75 wt%. The nonionic surfactant preferably has an (HLB) value of about 14 to about 18, preferably about 14 to about 17, preferably about 15 to about 18.

[0019] The nonionic polymerizable hydrophilic component, such as methoxy polyethylene glycol methacrylate or methoxy polypropylene glycol methacrylate, is preferably present in an amount of 0 wt % to about 10 wt % (i.e., less than 10 wt %), 0 wt % to about 5 wt % (i.e., less than 5 wt %), or preferably about 1.5 wt % to about 3.5 wt %. Alternatively, the nonionic polymerizable hydrophilic component is present in an amount of about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %.

[0020] In one embodiment, a small amount of anionic surfactant can be used to replace nonionic surfactant in the initial inoculation stage to better control the particle size of seed formation. The total amount of anionic surfactant can be from 0 wt % to about 0.25 wt %, preferably from 0.01 wt % to about 0.25 wt %, preferably from about 0.05 wt % to about 0.15 wt % based on the total monomer content. Alternatively, the range of anionic surfactants used in the inoculation process can be from 0.035 wt % to about 0.15 wt % based on the total monomer content. Without being limited to any particular theory, the inventors of the present invention believe that anionic surfactants are more effective in controlling particle size and are compatible with latex and cationic paints at low levels of anionic surfactants.

[0021] Without being bound by any particular theory, the inventors believe that the seeds polymerized using the anionic surfactant are covered by the monomers polymerized using the nonionic surfactant during the polymerization of the latex particles. In the nonionic latex resin of the present invention, the seeds formed using the anionic surfactant are chemically isolated, and the anionic seeds do not react with the cationic latex resin or the reaction level is insufficient to produce coarse particles, gels or other precipitated particles.

[0022] Alternatively, the seeds may be polymerized with a nonionic surfactant that produces a nonionic latex resin with a larger particle size. Alternatively, the seeds may be prepared separately, or may be purchased commercially and used for polymerization.

[0023] The percentages of the components of the nonionic resins described herein are given as weight percent of active ingredients, including the weight of solid monomers and active ingredients of additives, excluding water.

[0024] One embodiment of the present invention is directed to a substantially nonionic latex resin polymerized from:

[0025] A monomer mixture comprising at least one nonionic (meth)acrylate monomer, a polymerizable nonionic hydrophilic component, wherein the monomer mixture is substantially free of acid monomers or other monomers with anionic groups, and

[0026] a nonionic surfactant ranging from about 1 wt % to about 4 wt %, preferably from about 1.5 wt % to about 3.5 wt %; and

[0027] wherein the polymerizable hydrophilic component is present in an amount of about 1.5 wt % to about 3.5 wt %,

[0028] The weight percentages stated do not include water.

[0029] Another embodiment of the present invention relates to a substantially nonionic latex resin polymerized from:

[0030] A monomer mixture comprising at least one nonionic (meth)acrylate monomer, a polymerizable nonionic hydrophilic component, wherein the monomer mixture is substantially free of acid monomers or other monomers with anionic groups, and

[0031] A nonionic surfactant in the range of about 1 wt % to about 4.5 wt %, preferably about 1.25 wt % to about 4.25 wt %, preferably about 1.5 wt % to about 3.75 wt %, wherein the HLB value of the nonionic surfactant is in the range of about 14 to about 18, preferably about 14 to about 17, preferably about 15 to about 18,

[0032] wherein the polymerizable hydrophilic component is present in an amount of about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %,

[0033] The weight percentages stated do not include water.

[0034] Preferably, the monomer mixture does not contain acid monomers or other monomers with anionic groups. Alternatively, the acid monomers or other monomers with anionic groups are less than 0.25 wt%, preferably less than 0.125 wt% of the total monomer content.

[0035] In one embodiment, the substantially nonionic latex resin is further polymerized with an inoculum amount of anionic surfactant ranging from about 0.01 wt % to about 0.25 wt %, preferably from about 0.05 wt % to about 0.15 wt %, based on the total monomer content. Alternatively, the anionic surfactant ranges from about 0.035 wt % to about 0.15 wt %, based on the total monomer content.

[0036] Preferably, the polymerizable hydrophilic component comprises a polymerizable polyethylene glycol monomer or a polymerizable polypropylene glycol monomer. In one embodiment, the polymerizable polyethylene glycol monomer is a methoxy polyethylene glycol methacrylate monomer.

[0037] Preferably, the nonionic surfactant has an HLB value in the range of about 14 to about 18, preferably about 14 to about 17, preferably about 15 to about 18.

[0038] In certain embodiments, only nonionic surfactants are used in the polymerization to form micelles and the substantially nonionic latex resin.

[0039] Preferably, the present invention further relates to a paint or building composition comprising a substantially nonionic latex resin as described herein and at least one cationic additive. Preferably, the cationic additive is present in an amount of 1.0% to 6.0% by weight of the paint or building composition, preferably 2.0% to 4.5% by weight or 2.5% to 3.5% by weight, wherein the weight percentage of the cationic additive to the building composition includes water.

[0040] Preferably, the cationic additive has at least one positively charged metal ion. The at least one charged metal ion may be an aluminum cation or a zirconium cation or other cations.

[0041] The cationic additive may include at least one of poly(hydroxyaluminum) chloride, polymeric cationic quaternary amine, a blend of didecyldimethylammonium carbonate and didecyldimethylammonium bicarbonate, aluminum hydroxide, zirconium silicate, ammonium zirconium carbonate, potassium zirconium carbonate, and calcium strontium zinc phosphosilicate.

[0042] The paint or building composition preferably further comprises an acid. Preferably, the acid may be citric acid or sodium gluconate. Preferably, the acid is present in an amount of about 0.25 wt % to about 2.0 wt %, preferably about 0.5 wt % to about 1.5 wt %, or about 0.7 wt % to about 1.0 wt %, wherein the weight percentage of the acid to the building composition includes water.

[0043] Another embodiment of the present invention pertains to a process for polymerizing a nonionic resin, wherein the nonionic resin contains substantially no acid monomers or contains no acid monomers, the process comprising the steps of:

[0044] - polymerizing at least one or more film-forming nonionic monomers and a polymerizable hydrophilic component with at least one nonionic surfactant,

[0045] The nonionic surfactant ranges from about 1 wt % to about 4.5 wt %, preferably from about 1.25 wt % to about 4.25 wt %, preferably from about 1.5 wt % to about 3.75 wt %,

[0046] wherein the polymerizable hydrophilic component is present in an amount of about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %,

[0047] The weight percentages stated do not include water.

[0048] Optionally, the method further comprises the following steps:

[0049] The seeds of the nonionic resin are prepared using an inoculum amount of anionic surfactant, wherein the inoculum amount ranges from about 0.01 wt % to about 0.25 wt %, preferably from about 0.35 wt % to about 0.15 wt % or from about 0.05 wt % to about 0.15 wt % based on the total monomer content.

[0050] As used herein, "substantially nonionic latex resin" refers to a nonionic latex resin that is substantially free of acid monomers or monomers with anionic groups, and that may include an inoculum amount of anionic surfactant used in the inoculum stage of the polymerization process to control the particle size of the latex resin, as those terms are defined and used herein. Preferably, no acid monomers and no monomers with anionic groups are used in the polymerization of the nonionic resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In the accompanying drawings which constitute a part of the specification and are to be read in conjunction with the specification, like reference numerals are used to designate like parts throughout the several views:

[0052] Figure 1 are photographs of four test panels showing tannin stain, conventional primer and primer of the present invention, and topcoat.

[0053] Specific implementation methods of the preferred embodiment

[0054] Although capable of locking in stains and minimizing the ability of stains to migrate through a paint film, cationic resins can cause water sensitivity issues such as loss of wet adhesion, reduced scrub resistance, and reduced blister resistance due to their hydrophilic nature. As shown in the following experiments, cationic paints and primers suffer from water sensitivity such as blistering on the paint film when used alone. The present invention solves this problem by mixing a cationic additive or another tannin-reactive compound with a novel nonionic resin. The nonionic resin composition of the present invention is stable and advantageously compatible with cationic additives and tannin-reactive compounds, as well as cationic resins.

[0055] U.S. Pat. No. 4,981,759 discloses that a nonionic acrylic resin can be obtained by (co)polymerizing at least one unsaturated monomer selected from alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, propyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate, (meth)acrylic acid, aromatic vinyl compounds such as styrene and its derivatives (e.g., α-methylstyrene), (meth)acrylonitrile; and butadiene, depending on the desired properties.

[0056] Typical emulsion polymerizations (such as those described in the '759 patent) include acrylic, vinyl or styrene monomers, and a small amount of an acid monomer, such as (meth)acrylic acid, is added to stabilize the polymerization. Generally, in the absence of an acid monomer, the emulsion process is unstable and often unsuccessful. The inventors of the present invention have determined that the use of an acid monomer such as (meth)acrylic acid in the polymerization renders the resulting polymer anionic. Without being bound by any particular theory, it is believed that the side chains on the (meth)acrylic acid in the latex polymer lose protons and become anionic.

[0057] Parent U.S. Provisional Patent Application Serial No. 63 / 388,080, filed on July 11, 2022, discloses an anti-fouling building composition utilizing a cationic resin and a novel non-ionic resin blend that can resist the migration of stains through the paint film. The parent patent application is incorporated herein by reference in its entirety.

[0058] Without being limited to any particular theory, the inventors of the present invention have found that when a polymerizable nonionic hydrophilic component such as a polymerizable polyethylene glycol or a polymerizable polypropylene glycol is copolymerized with a film-forming monomer and a nonionic surfactant is used to form micelles, polymerization (preferably emulsion polymerization) can be carried out in the absence of an acid monomer. Preferably, only nonionic surfactants are used to form micelles and latex particles. Another aspect of the present invention relates to nonionic resins that are substantially free of acid monomers and preferably free of acid monomers.

[0059] According to one aspect of the present invention, the nonionic latex resin of the present invention is compatible with cationic functional groups. The nonionic latex resin of the present invention is mixed with a cationic additive to form a dried paint film having tannin barrier properties from the cationic functional groups of the cationic additive, and the dried paint film exhibits good film properties, such as anti-blistering. Suitable nonionic latex resins also have improved viscosity stability over their shelf life, as discussed below.

[0060] In a preferred embodiment of the present invention, acid monomers are preferably omitted or substantially omitted from the polymerization to prevent these moieties from forming anions on the polymer. In order to impart stability to the nonionic polymer resin, a hydrophilic nonionic surfactant is used in the polymerization. In addition, a polymerizable nonionic hydrophilic component such as a polymerizable polyethylene glycol or polypropylene glycol (e.g., methoxypolyethylene glycol methacrylate (molecular weight 750 Daltons, 50% in water) is added to the polymerization.

[0061] In a preferred embodiment, a small amount of anionic surfactant is added to the polymerization in order to seed the polymerization. The anionic surfactant is preferably the only ionic component in the polymerization and effectively seeds the latex polymer. If anionic surfactant is used, it is used at the inoculation stage at the beginning of the polymerization. Alternatively, a nonionic surfactant can be used during the inoculation process. Preformed or commercially available seeds can also be used; the monomer is polymerized around these seeds.

[0062] In less preferred embodiments, if acid monomer is used at all, it is preferably kept to less than 0.25 wt%, preferably less than 0.125 wt%, and preferably less than 0.1 wt% and more preferably 0 wt%.

[0063] Preferably, the nonionic surfactant is preferably present in an amount of 0 wt % to about 5 wt % (less than 5 wt %), preferably about 1 wt % to about 4 wt %, preferably about 1.5 wt % to about 3.5 wt %. Alternatively, the nonionic surfactant is present in an amount of about 1 wt % to about 4.5 wt %, preferably about 1.25 wt % to about 4.25 wt %, and preferably about 1.5 wt % to about 3.75 wt %. The anionic surfactant (if used) is preferably present in an amount of 0 wt % to about 0.25 wt %, preferably 0.01 wt % to about 0.25 wt %, preferably about 0.05 wt % to about 0.15 wt %. Alternatively, the range of anionic surfactants used in the inoculation process can be 0.035 wt % to about 0.15 wt % based on the total monomer content. Preferably, the nonionic polymerizable hydrophilic component is present in an amount of 0 wt % to about 10 wt % (less than 10 wt %), 0 wt % to about 5 wt % (less than 5 wt %) or about 1.5 wt % to about 3.5 wt %. Alternatively, the nonionic polymerizable hydrophilic component is preferably present at about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %. The percentages of the components of the nonionic resin are provided as weight percentages of active ingredients, including the weight of the active ingredients of solid monomers and additives.

[0064] The ratio between nonionic surfactant and nonionic polymerizable hydrophilic component is preferably 1:1 (by weight), and at most 1.5 or 2.0 or 3 parts by weight nonionic surfactant: 1 part by weight nonionic polymerizable hydrophilic component.

[0065] Example 1. Exemplary Inventive Nonionic Resins without Acid Monomers The reactor seed was added to a nitrogen purged 4-neck reactor and the temperature was then raised to 60°C. Next, 30 g of the premixed monomer emulsion was added to the reactor, followed by the redox initiator, the oxidizing agent tert-butyl hydroperoxide (70%) and the reducing agent FF6M solution. The mixture is then reacted for 15 minutes. The remaining monomer emulsion, oxidant solution and reductant solution are simultaneously fed into the reactor over a period of 3.5 hours. 15 grams of water are used to rinse the monomer emulsion flask. The latex formed in the reactor is maintained at 60°C for 1 hour. The reactor is cooled to 25°C and the biocide solution is subsequently added. The nonionic latex adhesive has a Flory-Fox glass transition temperature of -2°C and a measured minimum film-forming temperature of 0°C. The particle size is 242 nanometers. (Unless otherwise noted, the particle size of the latex particles is the average volume.) The solid content is 40.6%. In Example 1, the initiator is a redox pair (tBHP and BruggoliteFF6M).

[0066]

[0067]

[0068]

[0069] Example 2. Another exemplary inventive nonionic resin without acid monomers .The reactor seed was added to a nitrogen purged 4-neck reactor and the temperature was then raised to 80°C. Next, 31 g of the premixed monomer emulsion was added to the reactor followed by the seed initiator solution. The mixture was then allowed to react for 15 minutes. The remaining monomer emulsion was fed simultaneously to the reactor over a period of 3.5 hours. 30 g of water was used to rinse the monomer emulsion flask. The latex formed in the reactor was maintained at 80°C for 1 hour. The reactor was cooled to 60°C and tert-butyl hydroperoxide and FF6M solution. The reactor was then cooled to room temperature and the biocide solution was added. The nonionic latex binder had a Flory-Fox glass transition temperature of -2°C and a measured minimum film forming temperature of 0°C. The particle size of the latex was 249 nanometers. The solids content was 42.6%. In Example 2, the initiator was sodium persulfate.

[0070]

[0071]

[0072] Example 3A. Another exemplary invention nonionic resin without an acid monomer. Example 3A is disclosed in parent U.S. Provisional Patent Application Serial No. 63 / 388,080. The weight percentages reported in this example do not include water. Typically, MPEG 750MA is available in a 50% aqueous solution and the (meth)acrylate monomer is available as a 40-42 wt % solid in aqueous solution. A small amount of anionic surfactant is added to Example 3A to seed the polymerization. No acid monomers are copolymerized and sodium persulfate is the initiator.

[0073]

[0074]

[0075] Example 3B Similar to Example 3A, except it utilizes more nonionic surfactant during the polymerization process.

[0076]

[0077]

[0078] In Examples 3A and 3B, the glass transition temperature (Tg) of the nonionic resin ranges from about -5°C to about 15°C, preferably from about -5°C to about 5°C, with typical values ​​of 1°C to 10°C calculated using Fox's equation. The Fox calculation may ignore small components (e.g., less than 3 wt%) that do not have readily available Tg values, such as poly(ethylene or propylene) oxide or wet adhesion monomers. The minimum film forming temperature (MFFT) ranges from about -2°C to about 2°C, preferably from about -2°C to about 6°C, as determined by ISO 2115 standards. The particle size (mean volume, mV) is from about 155nm to about 175nm, and the pH is from about 5 to about 6.

[0079] Example 4. Another exemplary invention of nonionic resin without an acid monomer. The nonionic resin was prepared in the same manner as in Example 2 except that

[0080] - 1.5 g of ethoxylated tridecanol was replaced with 3.3 g of anionic phosphate surfactant (25% solids) for seeding, and

[0081] - The seed monomer mixture does not contain polyethylene glycol methacrylate. Polyethylene glycol methacrylate is added to the monomer emulsion after the seed monomer mixture is charged to the reactor.

[0082] Anionic surfactants comprise 0.11 wt% (solids); nonionic surfactants comprise 2.48 wt% (solids); and polyethylene glycol methacrylate comprises 1.91 wt% (solids). The polymer has a particle size of 164.9 nanometers. The polymer has a Flory-Fox glass transition temperature of -2°C and a minimum film forming temperature measured of 0°C. It has a solids content of 40.6%. Sodium persulfate is an initiator.

[0083] Example 5. Another exemplary invention of nonionic resin without an acid monomer. A nonionic copolymer resin was prepared similarly to Example 4, except that 80 grams of DAAM crosslinking monomer was added to the monomer mixture. Anionic surfactant accounted for 0.10 wt % (solids); nonionic surfactant accounted for 2.25 wt % (solids); and polyethylene glycol methacrylate accounted for 1.74 wt % (solids). The resin had a particle size of 168 nm and a solids content of 43.6%.

[0084] Example 6. Another exemplary invention of nonionic resin without an acid monomer. A nonionic copolymer was prepared similarly to Example 5, except that 80 grams of DAAM was replaced with 80 grams of AAEM crosslinking monomer. Anionic surfactant accounted for 0.10 wt % (solids); nonionic surfactant accounted for 2.25 wt % (solids); and polyethylene glycol methacrylate accounted for 1.74 wt % (solids). The resin had a particle size of 161 nm and a solids content of 44.0%.

[0085] Listed below is a summary of certain components and their particle sizes for Examples 1-6.

[0086]

[0087] As shown in Examples 1-6, when anionic surfactants are used during the inoculation process (Examples 3A, 3B, 4, 5 and 6), the particle size (mV) of the nonionic latex particles can be better controlled than when nonionic surfactants are used during the inoculation process (Examples 1 and 2).

[0088] It is worth noting that in Examples 1-6, the reported weight percentages are based on all solids. By excluding small amounts of solids, i.e., buffers, initiators, chasers, and biocides, the weight percentage of surfactant or MPEG based on total monomer content can be easily calculated. Since the weight percentage of surfactant based on total monomer content is determined, the surfactant will be included in the percentage calculation. The weight percentage based on total monomer content and the weight percentage based on total solids are essentially the same.

[0089] In Resin Examples 1-6, the nonionic surfactant has an HLB value of 14.5 or 16.3. The preferred HLB value range is from about 14 to about 18, preferably from about 14 to about 17, preferably from about 15 to about 18. Without being bound by any particular theory, a higher hydrophilicity is required to stabilize the latex particles because the nonionic nature of these latexes results in no static stability.

[0090] According to one aspect of the present invention, a cationic additive is mixed with a nonionic latex resin (preferably one or more of Examples 1 to 6 of the present invention). The cationic additive reacts with tannins and locks in tannins to minimize or prevent tannin stains from migrating to the topcoat of the paint film, and the nonionic latex resin of the present invention provides the paint film with good water resistance, such as anti-blistering.

[0091] Suitable cationic additives include those having positively charged metal ions such as aluminum or zirconium cations. Such cations chelate with the pendant phenolic groups in the tannins. Suitable cationic additives include, but are not limited to, poly(hydroxyaluminum) chlorides (PACs), also known as poly(aluminum chlorides), as tested in Example 7 as discussed below.

[0092] PAC is an inorganic chemical commonly used as a coagulant in wastewater treatment. PAC is reactive to tannins and can lock up tannins. PAC is commercially available under the trade name PAX by Kemira. Commercial PACs are available with different aluminum, aluminum oxide, chlorine contents and with various basicities. Exemplary PACs are PAX-14, PAX-18, PAX-XL6, PAX-XL8, and PAX-XL19, and their properties are listed below.

[0093] name Al(%) Al2O3(%) Cl(%) solid(%) Alkalinity(%) PAC1 (PAX-14) 7.1 13.4 21.0 41.5 25.5 PAC2 (PAX-18) 9.0 17.0 21.0 47.0 35.8 PAC3(PAX-XL6) 5.3 10.0 11.3 29.6 54.3 PAC4(PAX-XL8) 5.7 10.8 11.3 29.5 63.6 PAC5 (PAX-XL19) 12.6 23.7 8.3 44.6 84.2

[0094] As used herein, alkalinity is defined as known to those skilled in the art. The acidity and alkalinity of a compound are indicators of pH. The acidity of a medium is caused by acidic compounds, which can release hydrogen ions (H + ), resulting in a lower pH of the medium. The alkalinity of the medium is caused by basic compounds, which can release hydroxide ions (OH-), resulting in a high pH of the medium. In aqueous media, acidity causes low pH, while alkalinity causes high pH.

[0095] Suitable cationic additives also include cationic flocculants, which are polymeric cationic quaternary amines (CQAs) and are commercially available as Kemira Superfloc C572, C573, C569, and C-4007. C572, C573, and C-4007 have lower molecular weights, and C569 is a medium molecular weight polymeric quaternary amine.

[0096] Suitable cationic additives also include organic cationic compounds reactive toward tannins, such as a blend of didecyldimethylammonium carbonate and didecyldimethylammonium bicarbonate, which is used as 1000 is commercially available. This is a non-chloride quaternary ammonium salt that can be used as a corrosion inhibitor or a cationic surfactant.

[0097] Further suitable cationic additives include aluminum hydroxide, zirconium silicate, ammonium zirconium carbonate, potassium zirconium carbonate, calcium strontium zinc phosphosilicate. Commercially available cationic additives are available as Halox XTAIN A pigment and WPC tannin blocker.

[0098] exist Example 7 Inventive Example 7.E utilized the nonionic resin of Example 3 and the tannin reactive compound poly(hydroxyaluminum) chloride. Inventive Example 7.E was compared with Comparative Examples 7.A to 7.D. The results are shown below.

[0099] Examples 7.A. to 7.E

[0100]

[0101] - Cationic resin I used in this experiment is a commercial aqueous emulsion polymerized resin. Cationic resin II is a commercial aqueous hydrophilic solution polymerized resin. The cationic resin contains about 57% water. The nonionic resin is discussed in Example 3 and contains about 59% water.

[0102] - C / R is the contrast ratio. The contrast ratio is the ratio of the Y value of the paint on the stained area divided by the lightness (Y) value of the paint color on the non-stained area. The best C / R score is theoretically 100.

[0103] - Δb* is a measure of yellowness by measuring the intensity of light of a specific wavelength (e.g., the wavelength of yellow) with a spectrophotometer. The higher the reading, the more stain there is.

[0104] - Blistering resistance was tested at 90°C and rated from 1-5, with 1 being the worst and 5 being the best.

[0105] The results of Examples 7A-E show that the conventional anionic antifouling paint (Example 7.A) has acceptable anti-blistering properties, i.e., good wet adhesion, but poor antifouling capabilities compared to the benchmark Example 7.D. Conventional paints utilizing cationic resins (Examples 7.B and 7.C) exhibit good antifouling capabilities, but poor anti-blistering properties compared to the benchmark.

[0106] Inventive Example 7.E, which includes 3.4 weight percent of a poly(hydroxyaluminum) chloride additive, exhibits good stain resistance and excellent blister resistance. Additional inventive examples using the inventive nonionic polymer resins and cationic additives discussed herein are performed and discussed below. The inventors note that indoor blister resistance testing is rigorously conducted at 90°C, which far exceeds the environmental conditions to which paints and other building compositions are exposed. Nevertheless, the high pass (5.0 score) of Inventive Example 7.E indicates that the inventive paints have improved resistance to blistering at elevated temperatures, and the invention is not limited to any blister score. The inventive paints exhibit good tannin resistance and no coarse particles or gels are formed when the cationic additives are mixed with the inventive nonionic resins.

[0107] Example 8 Inventive paint examples 8.A-8.E were prepared using the nonionic resin of Example 1, and a polymeric cationic quaternary amine (CQA) and a blend of didecyl dimethyl ammonium carbonate and didecyl dimethyl ammonium bicarbonate (DDAMC), as shown below.

[0108]

[0109]

[0110] CQA1 has a medium molecular weight; CQA2, CQA3, and CQA4 have a low molecular weight.

[0111] The weight percentage of cationic additive (including water) in Example 8 is 2.83 wt%. The tannin blocking paint of Example 8 was applied to a cedar wood surface having a dark tannin stain band caused by a concentrated tannin solution. A commercial topcoat was applied over the tannin blocking paint of Example 8. For comparison, commercial anionic and cationic paints were applied over cedar wood. After the paints dried, optical measurements were taken using an optical spectrophotometer. The results are shown below.

[0112]

[0113]

[0114] As discussed with respect to Example 7, higher C / R values ​​and lower Δb* values ​​indicate better tannin barrier properties.

[0115] Figure 1 The photo in shows an exemplary tannin barrier test. First, condensed tannin was applied in strips to a cedar board. A primer was then applied over the tannin stain using a 3 mil drawdown bar. After drying for 1 day, a commercial topcoat was applied over the primer, albeit over a smaller area. After the topcoat dried, the contrast ratio (CR) and yellowness Δb* were measured on the topcoat over the tannin stain area and the tannin non-stained area. Figure 1 Of the four panels shown, the leftmost panel has a commercial anionic primer and a topcoat of a commercial anionic paint. The next left panel has a commercial cationic primer and the same commercial anionic topcoat. The two right panels have Primer 8.D, and the same commercial anionic topcoat is used on both right panels. Tannin stains are still visible on the primer ("tannin blocking paint"). However, they are "locked" to the panel by the primer 8.D of the present invention, and the stains are not visible on the topcoat. On the other hand, stains are visible on the topcoat of the two left panels with conventional primers.

[0116] The tannin barrier performance of the paint in Example 8 is better than that of a commercial anionic paint and is similar to that of a commercial cationic paint. As shown in Example 7, commercial cationic paints have poor water resistance and are prone to foaming.

[0117] Example 9 . The inventive paint examples 9.A-9.E were prepared using the nonionic resin of Example 1 and the cationic additives PAC1-PCA5, as shown below.

[0118]

[0119]

[0120] The weight percentage of the cationic additive (including water) in Example 8 was 2.76 wt %. A tannin barrier test was conducted in the same manner as in Example 8, and the results are shown below.

[0121]

[0122]

[0123] The tannin barrier performance of the paint in Example 9 is better than that of commercial anionic paints and is similar to that of commercial cationic paints.

[0124] Inventive Examples 8.A-8.E and Inventive Examples 9.A-9.E have comparable or better tannin barrier properties than commercial cationic paints, and have significantly better tannin barrier properties than commercial anionic paints. Examples 7.A-7.E show the same results, and show that Inventive Example 7.E has good blister resistance.

[0125] The cationic additives tested in Examples 7-9, namely poly(hydroxyaluminum) chlorides having different concentrations of aluminum, aluminum oxide, and chloride (PAC), polymeric cationic quaternary amines (CQA) having different molecular weights, and blends of dodecyldimethylammonium carbonate / bicarbonate, were shown to perform well relative to each other in blocking tannin migration or color bleeding. It is anticipated that other cationic additives, including, but not limited to, those listed herein, will perform equally well when mixed with the inventive nonionic latex resins described herein.

[0126] Preferably, the cationic additive is added to the paint / building composition utilizing the nonionic latex resin of the present invention at 1.0 wt % to 6.0 wt %, preferably 2.0 wt % to 4.5 wt %, and preferably 2.5 wt % to 3.5 wt %. The weight percentage of the cationic additive to the building composition includes water in the calculation.

[0127] Conventional cationic paints have poor compatibility with most raw materials used in coatings, resulting in flocculation. The paint of the present invention prepared using the nonionic resin and cationic additive of the present invention has good compatibility and no flocculation. Most cationic paints still have a tendency for their viscosity to gradually increase over time.

[0128] According to another aspect or embodiment of the present invention, an acid is added to the paint of the present invention to maintain the viscosity of the paint.

[0129] Example 10Paint Examples 10.A and 10.B were prepared using the same ingredients and methods as Example 9.E, with additional ingredients added to improve the stability of viscosity over time. More specifically, Example 10.A included 9.5 grams of citric acid, and Example 10.B included 9.5 grams of sodium gluconate, which accounted for 0.87% by weight (including water) (9.5 g÷(1087.1 g+9.5 g)). The results are shown below.

[0130]

[0131] Preferably, the acid is added to the nonionic paint / building composition mixed with the cationic additive in an amount of 0.25 to 2.0 wt %, preferably 0.5 to 1.5 wt %, and more preferably 0.7 to 1.0 wt %. The weight ratio of the acid to the building composition includes water in the calculation.

[0132] Exposure experiment. Wooden boards painted with commercial primers and primer blends of nonionic resins and cationic resins of the present invention were placed outdoors for two years to test the durability of the paint. Some painted boards were kept in a horizontal position, and some were kept at an angle of approximately 45° to the south. Some boards were also painted with a topcoat layer. Most of the primer paints remained good, and all primer and topcoat paints remained good. The growth of microbial organisms was observed on the boards painted with only commercial primers. Less growth or no growth was observed on the boards painted with the blends of nonionic resins and cationic resins of the present invention. The boards painted with the blends of nonionic resins and cationic resins of the present invention performed better in resisting microbial growth than the boards painted with the benchmark primer and commercial primers. The boards painted with the blends of nonionic resins and cationic resins of the present invention performed better in water sensitivity and adhesion than the boards painted with the benchmark primer, and had less cracking and peeling on the horizontally placed boards.

[0133] Generally speaking, any (meth)acrylic acid monomer can be used in the present invention. Suitable (meth)acrylic acid monomers include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylamide, alkyl (meth)acrylates such as methyl (meth)acrylate, (meth)acrylic acid, wet adhesion monomers such as N-(2-methacryloyl)methacrylate, The preferred monomers include divinylbenzene, diacrylates, alkyl ...

[0134] Preferred monomers containing aromatic groups are styrene and α-methylstyrene. Other suitable monomers containing aromatic groups include, but are not limited to, 2,4-diphenyl-4-methyl-1-pentene, 2,4-dimethylstyrene, 2,4,6-trimethylstyrene, 2,3,4,5,6-pentafluorostyrene, (vinylbenzyl)trimethylammonium chloride, 2,6-dichlorostyrene, 2-fluorostyrene, 2-isopropenylaniline, 3 (trifluoromethyl)styrene, 3-fluorostyrene, α-methylstyrene, 3-vinylbenzoic acid, 4-vinylbenzyl chloride, α-bromostyrene, 9-vinylanthracene, and combinations thereof.

[0135] Preferred monomers containing primary amide groups are (methyl) acrylamide. Suitable monomers containing amide groups include, but are not limited to, N-vinylformamide or any vinylamide, N,N-dimethyl (methyl) acrylamide, N-(1,1-dimethyl-3-oxobutyl) (methyl) acrylamide, N-(hydroxymethyl) (methyl) acrylamide, N-(3-methoxypropyl) (methyl) acrylamide, N-(butoxymethyl) (methyl) acrylamide, N-(isobutoxymethyl) acryl (methyl) acrylamide, N-[tris (hydroxymethyl) methyl] acryl (methyl) acrylamide, 7-[4-(trifluoromethyl) coumarin] (methyl) acrylamide, 3-(3-fluorophenyl)-2-acrylamide, 3-(4-methylphenyl) (methyl) acrylamide, N-(tert-butyl) (methyl) acrylamide and combinations thereof. These monomers can be polymerized with the acrylic monomers listed above. The general formula of vinyl (formamide) is:

[0136]

[0137] And the general formula of (meth)acrylamide is:

[0138]

[0139] Wherein R1 and R2 can be -H, -CH3, -CH2CH3 and other substituted organic functional groups, and R3 can be -H, alkyl or aryl.

[0140] In one embodiment, styrene monomers, such as styrene, methylstyrene, chlorostyrene, methoxystyrene, and the like, are preferably copolymerized with (meth)acrylamide monomers.

[0141] In one embodiment, the aqueous latex polymer may also contain a vinyl monomer. Monomers of this type suitable for use according to the present invention include any compound having a vinyl functional group (i.e., a -CH=CH2 group). Preferably, the vinyl monomer is selected from the group consisting of vinyl esters, vinyl aromatic hydrocarbons, vinyl aliphatic hydrocarbons, vinyl alkyl ethers, and mixtures thereof.

[0142] Suitable vinyl monomers include vinyl esters such as, for example, vinyl acetate, vinyl propionate, vinyl laurate, vinyl pivalate, vinyl nonanoate, vinyl decanoate, vinyl neodecanoate, vinyl butyrate, vinyl hexanoate, vinyl benzoate, vinyl isopropyl acetate and similar vinyl esters; nitrile monomers such as (meth) acrylonitrile and the like; vinyl aromatics such as, for example, styrene, methyl styrene and similar lower alkyl styrenes, chlorostyrene, vinyl toluene, vinyl naphthalene and divinylbenzene; vinyl aliphatic hydrocarbon monomers such as, for example, vinyl chloride and vinylidene chloride, and alpha olefins such as, for example, ethylene, propylene, isobutylene, and conjugated dienes such as 1,3-butadiene, methyl-2-butadiene, 1,3-pentylene, 2,3-dimethylbutadiene, isoprene, cyclohexene, cyclopentadiene and dicyclopentadiene; and vinyl alkyl ethers such as, for example, methyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether and isobutyl vinyl ether.

[0143] Additives may be added to the polymerization process including surfactants, initiators, chaser solutions, biocides, rheology modifiers, and the like.

[0144] JV Koleske, R. Springate, and D. Brezinski describe surfactants in the Additives Reference Guide, pp. 83-88 (2013), and these pages are incorporated herein in their entirety. The following discussion of surfactants is based on Koleske et al.

[0145] Nonionic surfactants usually refer to polyoxyethylene derivatives, although other surfactants also belong to this class. They are usually prepared by the addition reaction of ethylene oxide with a hydrophobic compound containing one or more active hydrogen atoms. Examples of such hydrophobic compounds are fatty alcohols, alkylphenols, fatty acids, fatty amines, alkanolamines, fatty mercaptans, fatty amines and certain polyols. The polyols may include oxypropylene polyols, polyesters, etc. These surfactants are uncharged and will not dissociate. Their surface active characteristics come from the oxyethylene portion of the molecule. The nature of the hydrophobe and the length of the oxyethylene chain both affect the surface active characteristics.

[0146] In general, these groups are weakly hydrophilic compared to the hydrophobic part of the molecule. Weak ester bonds and amide bonds are also present in many nonionic surfactants. Nonionic surfactants are generally compatible with ionic surfactants. For example, many nonionic surfactants work well with anionic surfactants. In such a combination, they give aqueous systems good freeze-thaw stability and are less detrimental to mechanical properties than ionic compounds. Nonylphenol ethoxylate (NPE) is a typical example of such a surfactant. Other examples are: octylphenol ethoxylate (OPE), secondary alcohol ethoxylates, trimethylnonanol ethoxylate (TMN), specialty alkoxylates, and amine ethoxylates. In emulsion polymerization, alkyl ether sulfates are one of the main surfactants necessary to provide micelle stabilization. Traditionally, these sulfates have been based on alkylphenol ethoxylates (APEO). Typically, emulsion polymerization uses two types of surfactants - one nonionic and the other anionic. Each provides a separate stabilization mechanism for micelles, but the combination provides better stabilization, especially as temperature increases. Nonionic surfactants create spatial separation between micelle groups, while anionic surfactants create charged repulsion between micelles. Nonionic surfactants generally perform well over a range of pH values, and their foams are generally smaller than anionic and cationic surfactants. However, in complex coating formulations, nonionic surfactants may not reduce surface tension as well as anionic or cationic surfactants. There are nonionic polymeric fluorochemical surfactants that can provide low surface tension in organic coating systems. The lower the surface tension, the better the coating wetting, leveling and spreading. Therefore, these are excellent wetting agents, leveling agents and flow control agents for a variety of water-based, solvent-based and high-solid coating systems. Most fluorosurfactants are soluble and compatible with most polymers and continue to be active throughout the drying or curing process. When used in water-based systems, they tend to reduce the water / organic interfacial tension and remain surface active in the organic part of the polymer system. There is also an anionic fluorosurfactant based on ammonium salts on the market that is soluble in water.

[0147] Anionic surfactants carry a negative charge on the hydrophilic portion of the molecule. They are typically phosphates, sulfates, and sulfonates. These surfactants may or may not contain oxyethylene chains in their structure. Examples of anionic surfactants are sulfosuccinates, dioctyl sulfosuccinate (DOSS), polyether sulfates, polyether sulfonates, polyether phosphates, sodium lauryl sulfate, and phosphate-modified alcohol-ethoxylates.

[0148] Surface-active phosphates are a class of anionic surfactants prepared by the reaction of alcohols with activated phosphoric acid derivatives (including phosphoric anhydride and acid chloride). Typically, commercial phosphate products consist of a mixture of monoesters, diesters, free phosphoric acid and free alcohols used in their preparation. The properties of the final phosphate product are primarily determined by the composition of the starting alcohol used and the four different substances. On the contrary, the properties of the final phosphate product can be customized by changing the alcohol used in the preparation and controlling the ratio of the four different components present in the final product. Phosphate surfactants are made in free acid form, but can also be neutralized to a salt form using any alkali (including sodium hydroxide, potassium hydroxide, ammonium hydroxide or any organic amine).

[0149] Typically, phosphate ester surfactants are added to the formulation during the paint preparation process - either at the grind or at letdown, depending on the formulation. These additives have also been tested as post-paint formulation additives and have shown comparable properties. It is presumed, and the focus of much research, that the use of phosphate ester surfactants prior to the paint formulation stage (using phosphate esters in emulsion polymerization and post-polymerization stabilizers or additives in pigment dispersion) should only benefit the final properties of the paint and reduce the deleterious effects of additional surfactants in the paint system.

[0150] Cationic surfactants carry a positive charge, and quaternary ammonium compounds are the most common cationic surfactants. Compounds such as alkyltrimethylammonium chloride are representatives of these surfactants.

[0151] The hydrophilic lipophilic balance (HLB) system is a numbering system for evaluating the relative hydrophilicity of surfactants. The system is based on an arbitrary numerical scale, wherein zero is designated as a surfactant of extreme hydrophobicity, and 20 is designated as a surfactant of extreme hydrophilicity. The numbers assigned to a surfactant represent a measure of the balance between its hydrophilic strength and hydrophobic strength. A surfactant with an HLB of 10 has a balance of lipophilic and hydrophilic groups.

[0152] Examples of initiator and chaser solutions useful in the polymerization process may include, but are not limited to, ammonium persulfate, sodium persulfate, azo initiators (such as azoisobutyronitrile), redox systems (such as sodium hydroxymethanesulfinate (sodium formaldehyde sulfoxylate; reducing agent) and tert-butyl-hydroperoxide (oxidizing agent)), and the like, and combinations thereof, typically in aqueous solution. Either or both of these components may optionally contain additional surfactants and / or pH adjusters if desired to stabilize the emulsion.

[0153] Examples of pH adjusters useful in the polymerization process may include, but are not limited to, ammonium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, ammonia, amines such as trimethylamine, triethylamine, dimethylaminoethanol, diethylaminoethanol, AMP-95, and the like, and combinations thereof. In some cases, compounds considered to be pH adjusters may be added for purposes other than adjusting pH, such as emulsion stabilization, but are still characterized herein as pH adjusters.

[0154] Polymer molecular weight controllers are intended to control (usually limit) the molecular weight of a growing polymer. Although polymer molecular weight controllers may include substances such as radiation, they are typically molecules added to a polymerization mixture. Examples of polymer molecular weight controllers include, but are not limited to, chain transfer agents (CTAs), for example, alkyl mercapto esters such as isooctyl mercaptopropionate, alkyl mercaptans, etc., and combinations thereof. Chain transfer agents typically act as polymer molecular weight controller molecules, for example, catalytically or consumably terminating growing polymer chains by also initiating new growing polymer chains. In this way, the amount of chain transfer agents can be adjusted to reduce the target polymer molecular weight in a set of polymerization systems, or alternatively, in combination with calculating the amount of initiator, the amount of chain transfer agents can be calculated to target a specific average polymer molecular weight (e.g., within a given range) of a polymerization system.

[0155] Although the exemplary embodiments of the present invention disclosed herein obviously achieve the above-mentioned purpose, it should be understood that those skilled in the art can design numerous modifications and other embodiments. Therefore, it should be understood that the appended claims are intended to cover all such modifications and embodiments, which will fall within the spirit and scope of the present invention.

Claims

1. A substantially nonionic latex resin polymerized from: A monomer mixture comprising at least one nonionic (meth)acrylate monomer, a polymerizable nonionic hydrophilic component, wherein the monomer mixture is substantially free of acid monomers or other monomers with anionic groups, and a nonionic surfactant ranging from about 1 wt % to about 4 wt %, preferably from about 1.5 wt % to about 3.5 wt %; and wherein the polymerizable hydrophilic component is present in an amount of about 1.5 wt % to about 3.5 wt %, The weight percentages stated do not include water.

2. A substantially nonionic latex resin polymerized from: A monomer mixture comprising at least one nonionic (meth)acrylate monomer, a polymerizable nonionic hydrophilic component, wherein the monomer mixture is substantially free of acid monomers or other monomers with anionic groups, and A nonionic surfactant in the range of about 1 wt % to about 4.5 wt %, preferably about 1.25 wt % to about 4.25 wt %, preferably about 1.5 wt % to about 3.75 wt %, wherein the HLB value of the nonionic surfactant is in the range of about 14 to about 18, preferably about 14 to about 17, preferably about 15 to about 18, wherein the polymerizable hydrophilic component is present in an amount of about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %, The weight percentages stated do not include water.

3. The substantially nonionic latex resin of claim 1 or 2, wherein the monomer mixture does not contain acid monomers or other monomers with anionic groups.

4. The substantially nonionic latex resin of claim 1 or 2, wherein the acid monomer or other monomers with anionic groups are less than 0.25 wt. %, preferably less than 0.125 wt. % of the total monomer content.

5. The substantially nonionic latex resin of claim 1 or 2, further comprising an inoculum amount of an anionic surfactant, the inoculum amount ranging from about 0.01 wt % to about 0.25 wt %, preferably from about 0.05 wt % to about 0.15 wt %, based on the total monomer content.

6. The substantially nonionic latex resin of claim 1 or 2, wherein the anionic surfactant ranges from about 0.035 wt% to about 0.15 wt% based on total monomer content.

7. The substantially nonionic latex resin of claim 1 or 2, wherein the polymerizable hydrophilic component comprises a polymerizable polyethylene glycol monomer or a polymerizable polypropylene glycol monomer.

8. The substantially nonionic latex resin of claim 7, wherein the polymerizable polyethylene glycol monomer is a methoxy polyethylene glycol methacrylate monomer.

9. The substantially nonionic latex resin of claim 1, wherein the nonionic surfactant has an HLB value ranging from about 14 to about 18, preferably from about 14 to about 17, preferably from about 15 to about 18.

10. The substantially nonionic latex resin of claim 1 or 2, wherein only nonionic surfactant is used in the polymerization to form micelles and the substantially nonionic latex resin.

11. A paint or building composition comprising the substantially nonionic latex resin according to any one of claims 1 to 10 and at least one cationic additive.

12. The paint or building composition of claim 11, wherein the cationic additive is present in an amount of 1.0 to 6.0 wt. % of the paint or building composition, preferably 2.0 to 4.5 wt. % or 2.5 to 3.5 wt. %, The weight percentage of the cationic additive to the building composition includes water.

13. The paint or building composition of claim 11 wherein the cationic additive has at least one positively charged metal ion.

14. The paint or building composition of claim 13, wherein the at least one charged metal ion is an aluminum cation or a zirconium cation.

15. The paint or building composition of claim 11, wherein the cationic additive comprises at least one of poly(hydroxyaluminum) chloride, polymeric cationic quaternary amine, a blend of didecyldimethylammonium carbonate and didecyldimethylammonium bicarbonate, aluminum hydroxide, zirconium silicate, ammonium zirconium carbonate, potassium zirconium carbonate, and calcium strontium zinc phosphosilicate.

16. The paint or building composition of claim 11 further comprising an acid.

17. A paint or building composition as claimed in claim 16 wherein the acid comprises citric acid or sodium gluconate.

18. The paint or construction composition of claim 16 or 17, wherein the acid is present in an amount of about 0.25 wt % to about 2.0 wt %, preferably about 0.5 wt % to about 1.5 wt %, or about 0.7 wt % to about 1.0 wt %, The weight percentage of the acid to the building composition includes water.

19. A method for polymerizing a nonionic resin, wherein the nonionic resin contains substantially no acid monomers or contains no acid monomers, the method comprising the steps of: - polymerizing at least one or more film-forming nonionic monomers and a polymerizable hydrophilic component with at least one nonionic surfactant, The nonionic surfactant ranges from about 1 wt % to about 4.5 wt %, preferably from about 1.25 wt % to about 4.25 wt %, preferably from about 1.5 wt % to about 3.75 wt %, wherein the polymerizable hydrophilic component is present in an amount of about 1 wt % to about 5 wt %, preferably about 1.25 wt % to about 4.5 wt %, preferably about 1.5 wt % to about 3.5 wt %, preferably about 1.75 wt % to about 3.25 wt %, The weight percentages stated do not include water.

20. The method of claim 19, further comprising the steps of: The seeds of the nonionic resin are prepared using an inoculum amount of anionic surfactant, wherein the inoculum amount ranges from about 0.01 wt % to about 0.25 wt %, preferably from about 0.35 wt % to about 0.15 wt % or from about 0.05 wt % to about 0.15 wt % based on the total monomer content.

Citation Information

Patent Citations

  • Coating method

    US4981759A

  • Cationic latex coatings

    US5312863A